Reconfigurable computing: architectures, tools and applications 7th international symposium, ARC 2011, Belfast, UK, March 23-25, 2011 : proceedings - Koch, Andreas 1970 October 1. (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 7th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2011, held in Belfast, UK, in March 2011. The 40 revised papers presented, consisting of 24 full papers, 14 poster papers, and the abstracts of 2 plenary talks, were carefully reviewed and selected from 88 submissions. The topics covered are reconfigurable accelerators, design tools, reconfigurable processors, applications, device architecture, methodology and simulation, and system architecture.